A comprehensive analysis of China's regional energy saving and emission reduction efficiency: From production and treatment perspectives. (September 2015) - Wu, Jie; Lv, Lin; Sun, Jiasen; Ji, Xiang
Abstract: Energy and environmental issues have recently aroused increasing interest in China and many approaches are used to evaluate energy and environmental performance. In this paper, a two-stage network DEA framework is applied to evaluate the efficiency of energy saving and emission reduction in China during the period of the eleventh five-year plan, from 2006 to 2010. In this study, economic activities are divided into production and treatment processes. This is different from previous research which generally focused on either environmental efficiency or energy efficiency, omitting the integration of energy and environmental measures. Today, energy saving and emission reduction are both parts of the basic state policy of China and are equally important. The empirical results in this study show that: (i) eastern China has the best energy saving and emission reduction efficiency, performing is better than western and central China. (ii) The efficiency of the production process in central China is better than that in western China while the western area performs better than the central area in term of treatment efficiency. (iii) Integrated efficiency of energy saving and emission reduction of China was relatively stable in the five years and the pollution treatment efficiency maintained a rising trend. Highlights: We measured China's regional energy saving and emission reduction efficiency using two-stage DEA approach. The production and treatment processes are incorporated in evaluation. Eastern China performs best in terms of energy saving and emission reduction efficiency. Integrated efficiency of energy saving and emission reduction of China kept a stable trend during 2006–2010.